Analysis of Characteristics of Final Semester Examination Questions for Class IX Mathematics Using Rasch Model Theory in the Tidore Islands Region - Pramono, Aji Joko Budi; Jawa, Yani (International Journal of Education, Information Technology, and Others, 2023)
This study aims to analyze the characteristics of grade IX mathematics exam questions in the Tidore Islands region, North Maluku, using a quantitative descriptive methodology approach. Involving ninth grade junior high school students in North Maluku, this study used the Rasch Model approach based on the R program to analyze the quality of the items, including the unidimensional assumption test, item difficulty test, student ability test and item information value test. The instrument used was a test form from the mathematics subject. The results showed that the application of item response theory in analyzing Mathematics Final Semester Examination data was successful, with 11 factors and 1 dominant factor supporting the assumption of unidimensionality. The focus on the difficulty level of the questions showed that most of the questions were in the good range, effective in differentiating students' abilities. Analysis of the item characteristic curves provided insight into the quality of item design, while the accuracy of these curves, as per the Rasch model, is key in improving measurement validity. Thus, the results of this study are significant in improving understanding of the characteristics of grade IX mathematics items in the tidore islands region